Morphology and viability of castor bean genotypes pollen grains (Acta Scientiarum. Agronomy, 2016)
The objective of this work was to characterize the morphology and viability of the pollen of 15 genotypes of castor bean (Ricinus communis L.) and to generate information that can assist in the selection of highly promising male parents for future use in genetic improvement programs aimed at producing seeds for oil extraction. Acetolysis and scanning electron microscopy was used to characterize the morphology of the pollen. The viability of the pollen grains was estimated by in vitro germination and colorimetric analysis (acetocarmine 2% and 2, 3, 5-triphenyltetrazolium chloride 1%). For the in vitro germination, pollen grains were grown in 10 types of solidified culture medium consisting of different concentrations of sucrose, boric acid, calcium nitrate, magnesium sulfate and potassium nitrate. The pollen grains had the following characteristics: medium size, isopolar and subspheroidal shape, radial symmetry, circular ambit, 3-colporate, elongated endoapertures, tectate exine and granulated sexine. The acetocarmine dye overestimated pollen viability. The media M5 and M8 were the most efficient at promoting the germination of pollen grains. The studied genotypes had high levels of viability and can therefore be used as male parents in genetic improvement programs.